2011
DOI: 10.1111/j.1747-0285.2011.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

A Disalicylic Acid‐Furanyl Derivative Inhibits Ephrin Binding to a Subset of Eph Receptors

Abstract: Eph receptor tyrosine kinases and ephrin ligands control many physiological and pathological processes, and molecules interfering with their interaction are useful probes to elucidate their complex biological functions. Moreover, targeting Eph receptors might enable new strategies to inhibit cancer progression and pathological angiogenesis as well as promote nerve regeneration. Because our previous work suggested the importance of the salicylic acid group in antagonistic small molecules targeting Eph receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 69 publications
3
28
0
Order By: Relevance
“…Although the 12-amino acid KYL peptide was able to block the EphA4 signaling effectively, there may be huge challenges to develop this peptide as a drug candidate, e.g., bioavailability. For the identified small-molecule EphA4 inhibitors, although their effectiveness was demonstrated in in vitro or cellular assays, the in vivo effects of these compounds on inhibiting EphA4 and the bioavailability of these agents have not been reported (28,33,41). The reduction of EphA4 activation in APP/PS1 mouse brains by oral administration of Rhy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 12-amino acid KYL peptide was able to block the EphA4 signaling effectively, there may be huge challenges to develop this peptide as a drug candidate, e.g., bioavailability. For the identified small-molecule EphA4 inhibitors, although their effectiveness was demonstrated in in vitro or cellular assays, the in vivo effects of these compounds on inhibiting EphA4 and the bioavailability of these agents have not been reported (28,33,41). The reduction of EphA4 activation in APP/PS1 mouse brains by oral administration of Rhy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Combined efforts of high through-put screening and structural analyses have identified the derivatives of salicylates and lithocholic acid as small molecule inhibitors capable of disrupting Eph receptor-ligand interactions. Several salicylates were found to target the binding pocket of EphA4 as well as inhibiting ephrin binding to EphA2 and EphA4 (62, 63). These compounds inhibit a subset of Eph receptor activation and endothelial capillary-like tube formation in cell-based assays.…”
Section: Small Molecular Antagonists or Agonists Of Eph Receptormentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) characterization was consistent with the binding of the two salicylates in the ephrin-binding pocket of EphA4 and cell-based assays suggested that the compounds inhibit ephrin-dependent EphA2 and EphA4 activation and biological responses, although with low potency [25,40]. However, recent studies have revealed that some modification of the original compounds, which may involve polymerization or oxidative processes, is required for their inhibitory activity [41]. …”
Section: Small Molecules That Bind To Eph Receptors and Inhibit Epmentioning
confidence: 93%
“…A small molecule containing two salicylic acid-furanyl groups was also found to target the ephrin-binding pocket of EphA4 and inihibit ephrin binding to EphA2, EphA4 and several other Eph receptors through a mechanism that may involve irreversible binding [41]. The ability of the three salicylates to inhibit the activation of a subset of Eph receptors and their effects in cells, including endothelial capillary-like tube formation, suggest that these compounds could be used as chemical tools to study Eph receptor functions.…”
Section: Small Molecules That Bind To Eph Receptors and Inhibit Epmentioning
confidence: 99%